Abraham in the Book of Jubilees : the rewriting of Genesis 11:26-25:10 in the Book of Jubilees 11:14-23:8 - Ruiten, J. van (Supplements to the Journal for the Study of Judaism, 2012)
In Abraham in the Book of Jubilees , Jacques van Ruiten offers a systematic analysis of one of the most important and extensive Second Temple Jewish treatments of the figure of Abraham (Jub. 11:14-23:8). Given the importance of representations and reinterpretations of Abraham within Judaism, Christianity, and Islam, a careful analysis of this early source is an important contribution to research both on the evolving images of biblical patriarchs and on the history of biblical interpretation. There are many references to Jubilees in articles and books on images of Abraham. They are chosen for exegetical motifs, with little attention for its own literary and narrative dynamics, or for the specific writing and reading practices that it embodies and attests. Van Ruiten's careful analysis thus provides important context and corrective.